2019
DOI: 10.1371/journal.pone.0226619
|View full text |Cite
|
Sign up to set email alerts
|

Lowbush blueberry fruit yield and growth response to inorganic and organic N-fertilization when competing with two common weed species

Abstract: Inorganic N fertilizers are commonly used in commercial blueberry fields; however, this form of N can favor increased weed species’ growth, which can ultimately reduce the benefits of fertilization. We hypothesized that chipped ramial wood (CRW) compost is an effective alternative organic fertilizer for blueberry plants when weeds are present, as ericaceous shrub species are generally more efficient in utilizing organic N than herbaceous weed species. In this study, we measured the growth, fruit yield, and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“… Yield ranges of lowbush blueberry reported in the literature compared to yield range in the present study [ 2 , 3 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 24 , 38 , 58 , 59 , 60 ]. …”
Section: Figuresupporting
confidence: 52%
See 3 more Smart Citations
“… Yield ranges of lowbush blueberry reported in the literature compared to yield range in the present study [ 2 , 3 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 24 , 38 , 58 , 59 , 60 ]. …”
Section: Figuresupporting
confidence: 52%
“…While regional N recommendation averaged 45 kg N ha −1 [ 38 ], nitrogen dosage appeared to be highly site-specific. A fertilizer trial in Nova Scotia, Canada, indicated optimum dosage of 35 kg N ha −1 , 40 kg P ha −1 , and 30 kg K ha −1 [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The N, P, and K doses varied in the range of 0-90 kg N ha-1, 0-39 kg P ha-1, and 0-75 kg K ha-1. Because weeds strongly impact leaf nutrient concentrations and fruit yield of lowbush blueberry [32], all trials were realized in weed-controlled environments according to local recommendations [33].…”
Section: Methodsmentioning
confidence: 99%